The Intersection of Genitopatellar Syndrome and Oral Health: A Case Report at Saudi Arabia - Sara Alzanbaqi; Ahmed Ghibban; Zuhair S. Natto (Case Reports in Dentistry)
Genitopatellar syndrome (GPS) is a rare genetic disorder characterized by a spectrum of clinical manifestations including the absence of patellae, psychomotor retardation, congenital flexion deformity of the lower limbs, and genitourinary abnormalities. A 5-year-old female presented to the Faculty of Dentistry Clinic for a routine dental examination. Physical examination revealed distinctive phenotypic features, notably wide thumbnails and limb wrinkling, while facial appearance appeared within normal limits. At birth, the patient exhibited dysmorphic clubfoot, genital anomalies, bilateral hydronephrosis, and hepatomegaly. Subsequent MRI evaluation disclosed bilateral dysplastic femoral trochlea with lateral patellofemoral dislocation, accompanied by marked tibial rotation and vertical talus. Additionally, bilateral hindfoot valgus deformity and first metatarsophalangeal joint flexion deformity were noted. Molecular analysis using Sanger sequencing identified a de novo heterozygous nonsense mutation (c.4117, p.Glu1373Ter) in the KAT6B gene. Oral examination revealed shortened clinical crowns, absence of caries in the primary teeth, and delayed eruption of the primary canines (Cs) and second molars (Es). Radiographic assessment demonstrated existing primary Es and incisors with delayed eruption. This report elucidates a potential association between GPS and oral manifestations, particularly highlighting delayed eruption of primary Es. Since there is a scarcity of publications addressing the oral and dental manifestations of the syndrome, this clinical case contributes, albeit not specifically, to the diagnosis.